Anaplastic carcinoma of thyroid: with osteoclast like giant cells: an extremely unusual finding in fine needle aspiration cytology - Vimal, Mourouguessine; Chitra, Tukkaram (International Journal of Research in Medical Sciences, 2016)
Anaplastic carcinoma of thyroid is a very rare malignant entity with aggressive behaviour. The FNAC finding of Osteoclast like giant cell in this malignancy is a very rare event with only hand full of cases are reported in the literature. This case report highlights the significance of cytological diagnosis of Anaplastic carcinoma of thyroid with Osteoclast like giant cell in a 70 year old man using simple FNAC technique and its role in determining the treatment plan.